The Continuing Advance and Retreat of Rural Settlement in the Northern Inland of Sweden - Carson, Dean; Lundmark, Linda; Carson, Doris (Journal of Northern Studies, 2020)
In 1960, a range of leading rural geographers started a debate about population development and the “advance and retreat” of human settlement in sparsely populated rural areas, including in the inland north of Sweden. In what came to be known as the “Siljan Symposium,” they identified a number of key themes in relation to migration and human mobility that were thought to determine settlement patterns in the inland north, including: internal migration and urbanisation of populations; the role of simultaneous in- and out-migration in re-shaping settlement patterns; redistribution of rural populations through return migration and international migration; and changing preferences for settlement in different northern “zones” based on the methods for exploiting natural resources for agriculture, forestry, mining and energy production. This paper re-visits the main themes from the 1960 Siljan Symposium and examines Swedish register data to identify how migration patterns and the resulting “advance and retreat” of human settlement have changed across the inland of Västerbotten and Norrbotten. The results suggest that, while general urban-rural and regional-local settlement patterns appear to have been relatively consistent, new forms of migration (including internal, return and international) with different preferences for rural settlement emerging in different localities as a result of both persistent (mining, forestry, energy) and changing (tourism, lifestyle) values of natural resources. We also observe substantial differences in migration and urbanisation rates between Norrbotten and Västerbotten. The paper then discusses how the persistence and discontinuity of experiences over the past decades may provide insights into the potential future patterns of northern settlement.